MEMBENTUK MAHASISWA MANDIRI MELALUI LITERASI KEUANGAN DAN INCOME GENERATING - Ulfah, Maria; Syahrudin, Husni (Jurnal Pengabdian Masyarakat Khatulistiwa, 2024)
ABSTRACTIt is incumbent upon students to develop the capacity to manage their personal finances, a necessity particularly for those who live at a distance from their parents. Students' autonomy in financial management is frequently constrained by reliance on parental financial assistance and the formation of detrimental spending habits. This initiative is designed to equip students with the knowledge and skills necessary to effectively navigate their financial affairs. The objective of this service is to enhance students' financial literacy and capabilities in income generation through entrepreneurial training programs. The implementation method comprises lectures on financial literacy and income generation, followed by the creation of products and their subsequent marketing by students in groups. The evaluation of this service is conducted through a response questionnaire and business reports for each group. The results demonstrate an increase in students' understanding of financial literacy and entrepreneurial skills, although the profits from their businesses remain relatively modest. From this activity, students gain a deeper comprehension of financial management and gain valuable experience in entrepreneurship. To enhance the efficacy of this initiative, it is recommended to establish dedicated entrepreneurship facilities on campus and to seek guidance from lecturers and entrepreneurship mentors.Keywords: Financial literacy, entrepreneurship, students, financial management, and generating incomeÂ ABSTRAKSebagai mahasiswa seharusnya mampu mengatur keuangan pribadinya, terutama yang tinggal jauh dari orang tuanya. Kemandirian mahasiswa dalam mengelola keuangan sering kali terhambat oleh ketergantungan pada kiriman uang dari orang tua dan kebiasaan buruk dalam belanja oleh karena itu kegiatan ini dimaksudkan untuk membekali mahasiswa wawasan agar meningkatkan pemahaman mahasiswa dalam mengelola pengeluaran. Pengabdian ini berfokus pada peningkatan literasi keuangan dan keterampilan mahasiswa dalam menghasilkan pendapatan melalui program pelatihan wirausaha. Metode pelaksanaannya antara lain melakukan ceramah dtentang literasi keuangan dan income generating (penghasilan tambahan) kemudian mahasiswa secara kelompok membuat produk dan memasarkankannya. Evaluasi pengabdian ini yaitu angket respon dan laporan usaha masing masing kelompok. Hasil evaluasi menunjukkan peningkatan dalam pemahaman siswa mengenai literasi keuangan dan keterampilan kewirausahaan, meskipun keuntungan dari usaha mereka masih kecil. Dari kegiatan ini mahasiswa lebih paham mengelola keuangan dan memiliki pengalaman tambahan dalam wirausaha. Untuk meningkatkan efektivitas, disarankan untuk menciptakan fasilitas kewirausahaan di kampus dan mencari dukungan dari dosen dan mentor kewirausahaan.Kata Kunci: Literasi keuangan, kewirausahaan, mahasiswa, pengelolaan keuangan, income generating.